2007
DOI: 10.1111/j.1467-9477.2007.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Television Debates in Multiparty Systems affect Viewers? A Quasi‐ experimental Study with First‐time Voters

Abstract: Television debates have become the centre stage for political debate in advanced societies. Although presidential debates in the United States have achieved much attention, the same cannot be said of the more typical panel debates in multiparty systems. This article investigates whether winning or losing panel debates matters in that it influences important attitudes among the electorate. Based on a quasi‐experimental design prior to the 2001 Norwegian parliamentary election, this study finds that the outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…Van der Brug (2004) asked respondents to estimate the importance that Dutch parties devote to various issues: 'I would like to ask you, according to you, how important or unimportant various issues are for the various parties.' Similarly, Aalberg and Jenssen (2007), asked in Norway 'In your opinion, which party is most engaged with [ISSUE]?' The most recent Swiss national election study, as reported by Lachat (2014), also contains an associative question: 'Which party cares the most about [ISSUE]?'…”
Section: Similar Competence Measurements and Measurement Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van der Brug (2004) asked respondents to estimate the importance that Dutch parties devote to various issues: 'I would like to ask you, according to you, how important or unimportant various issues are for the various parties.' Similarly, Aalberg and Jenssen (2007), asked in Norway 'In your opinion, which party is most engaged with [ISSUE]?' The most recent Swiss national election study, as reported by Lachat (2014), also contains an associative question: 'Which party cares the most about [ISSUE]?'…”
Section: Similar Competence Measurements and Measurement Problemsmentioning
confidence: 99%
“…Aalberg and Jenssen (2007) ask 'Which party has the best policy on [ISSUE]?' A similar observation applies to Green and Hobolt (2008) ('has the best policies on each problem'), Brasher (2009) ('has the best ideas'), Lachat (2014) ('has the best solutions'), and Dahlberg and Martinsson (2011) as well as Martinsson et al (2013) ('has the best politics').…”
Section: Similar Competence Measurements and Measurement Problemsmentioning
confidence: 99%
“…Kleinnijenhuis et al (2003) showed that the LFP headed by the populist leader Pim Fortuyn in the 2001 elections in the Netherlands managed to successfully claim and appropriate the immigration issue previously owned by the liberal party VVD. Aalberg and Jenssen (2007) studied, in a quasi-experiment, how preelectoral TV debates in the Norwegian multiparty system measurably affected and changed parties' status on issues: Parties that did well in the debate could significantly enhance their credibility on the debated issue, and the "winning" party was considered as better able to deal with the issue. Note that this study is one of the very rare in which issue ownership is considered as the dependent variable, as something that is to be explained; by far most previous research does not consider issue ownership as something that must be explained but rather as something that allows other things to be explained, mainly voting behavior.…”
Section: Issue Ownership Dynamics: Theory and Hypothesesmentioning
confidence: 99%
“…This might be due to a strong correlation between party preferences and party performance. 6 This question refers to the quality of recent 'proposals' rather than to handling abilities, an approach commonly followed in previous research (though see Aalberg and Jenssen 2007;Green andHobolt 2008 andLachat 2014;Walgrave et al 2015). We decided on this question wording based on cognitive pretesting (Wagner and Zeglovits 2014), which showed that respondents struggled less when asked about 'proposals' than when asked about the party 'best/worst at dealing with issue X,' perhaps because thinking about past actions is more concrete than considering hypothetical handling abilities.…”
mentioning
confidence: 99%